2021
DOI: 10.1080/21655979.2021.1971503
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA PCED1B antisense RNA 1 promotes gastric cancer progression via modulating microRNA-215-3p / C-X-C motif chemokine receptor 1 axis

Abstract: Long non-coding RNAs (lncRNAs) emerge as vital modulators and tissue-specific biomarkers of multiple cancers, including gastric cancer (GC). Instead, the expression characteristics, biological function and molecular mechanism of lncRNA PCED1B antisense RNA 1 (PCED1B-AS1) in GC await more elaboration. In this study, 48 cases of GC tissues and matched non-cancerous tissues were collected, and PCED1B-AS1, microRNA-215-3p (miR-215-3p) and C-X-C motif chemokine receptor 1 (CXCR1) expression levels were detected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…Additionally, this study observed that PCED1B-AS1 significantly attenuated the upregulation of MCP-1 induced by the CoCl 2 or TNF-α in Müller cells. Our findings are in agreement with previous studies which demonstrated that PCED1B-AS1 modulates chemokine receptors and immunosuppression [ 38 , 39 ]. The fact that PCED1B-AS1 had no effect on the upregulation of MCP-1 induced by the 25mM glucose may indicate that PCED1B-AS1 has a particular influence on the oxidative stress induced by continuous high glucose, instead of high glucose itself.…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, this study observed that PCED1B-AS1 significantly attenuated the upregulation of MCP-1 induced by the CoCl 2 or TNF-α in Müller cells. Our findings are in agreement with previous studies which demonstrated that PCED1B-AS1 modulates chemokine receptors and immunosuppression [ 38 , 39 ]. The fact that PCED1B-AS1 had no effect on the upregulation of MCP-1 induced by the 25mM glucose may indicate that PCED1B-AS1 has a particular influence on the oxidative stress induced by continuous high glucose, instead of high glucose itself.…”
Section: Discussionsupporting
confidence: 94%
“…LncRNA NORAD promotes gastric cancer cell proliferation by regulating miR-608 and affecting FOXO6 protein expression [ 19 ]. Ren et al [ 20 ] reported that PCED1B-AS1 accelerated GC progression via adsorbing miR-215-3p and up-regulating CXCR1, indicating that PCED1B-AS1 is a novel therapeutic target for treating GC. Likewise, we further studied the downstream miRNAs of lncRNA PCED1B-AS1 and found specific binding sites between PCED1B-AS1 and miR-3681-3p.…”
Section: Discussionmentioning
confidence: 99%
“…At 24 h after completion of transfection, all cells (KD‐KIF2A, KD‐NC, blank) were treated with capecitabine (Sigma‐Aldrich) and oxaliplatin (Sigma‐Aldrich), respectively. The concentrations of chemotherapeutic agents were set partly according to a previous study 19 with some modification as follows: capecitabine, 0, 100, 200, 400, 800, 1600, and 3200 μg/ml; oxaliplatin, 0, 0.2, 0.4, 0.8, 1.6, 3.2, and 6.4 μM. For the determination of drug sensitivity of cells, the relative cell viability at each drug concentration was measured after treatment for 48 h, with the use of Cell Counting Kit‐8 (Beyotime) according to the instruction of the kit.…”
Section: Methodsmentioning
confidence: 99%